Laughing Through Heritage: The Role of Aceh Pungo in Sustaining Acehnese Identity - Athifa Radella Tabina; Nuriza Dora (Indonesian Journal of Education and Social Studies, 2025)
This research aims to understand the role of Aceh Pungo in maintaining the cultural identity of the Acehnese people in the midst of globalization and modernization. The term "Aceh Pungo" which is often misinterpreted as "Aceh Gila" actually reflects the character of the Acehnese people who are critical, courageous, and humorous in responding to various social, political, and religious problems. This study uses a qualitative approach with a descriptive method through observation, interviews, and documentation of the Acehnese people involved in the Aceh Pungo tradition. The results of the study show that Aceh Pungo plays an important role in preserving the language, social values, and cultural expression of Aceh through art, humor, and social criticism. Strong Islamic values are also the foundation in every form of cultural expression. Traditions such as kenduri, peusijuek, and saman dance became a medium to strengthen the identity and social solidarity of the community. Although the younger generation faces challenges due to modernization, the Aceh Pungo community has managed to integrate local culture with digital media as a new form of adaptation in the preservation of cultural heritage. This study confirms that Aceh Pungo is not a symbol of madness, but a representation of cultural intelligence and the determination of the Acehnese people in defending their identity.